2020
DOI: 10.1590/1980-265x-tce-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: Nursing Care for Safety in the Mobile Pre-Hospital Service

Abstract: ABSTRACT Objective: to describe the actions performed by nurses from the mobile pre-hospital service before, during, and after consultations and transfers of suspected and/or confirmed patients of Covid-19, and the limitations found by these professionals on reducing exposure to the disease. Method: a descriptive-reflective study about the actions performed by nurses from the mobile pre-hospital service in a capital city in southern Brazil to increase safety during consultations or transfers of suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
41

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 8 publications
0
15
0
41
Order By: Relevance
“…However, after the start of cases and deaths in the country, Coordination became the best rated factor by the teams in the UEs, making it possible to infer that, in the face of a national public health emergency, coordinated actions are taken to prevent and control the pandemic, ensuring the safety of the professionals and patients. 24 Inter-professional coordination, as well as collaboration, requires the sharing of responsibilities between team members, interdependence, clarity of professional roles, tasks and objectives 3 to conduct health care through attributes considered indispensable in the context of unpredictability brought about by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, after the start of cases and deaths in the country, Coordination became the best rated factor by the teams in the UEs, making it possible to infer that, in the face of a national public health emergency, coordinated actions are taken to prevent and control the pandemic, ensuring the safety of the professionals and patients. 24 Inter-professional coordination, as well as collaboration, requires the sharing of responsibilities between team members, interdependence, clarity of professional roles, tasks and objectives 3 to conduct health care through attributes considered indispensable in the context of unpredictability brought about by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…54 Particularly in Brazil, most health services do not have experience of working in major emergencies, as is the case with COVID-19, which represents an additional stressor for the teams. 6 Thus, there is a strong need for strategies to support this category of workers, since mental health, in addition to being part of the sustainable development goals of the millennium, 64 also articulates with the goal of the 2030 agenda, which foresees the need for nine million nurses and midwives to achieve universal health coverage. 63 Before the advent of the COVID-19 pandemic, Brazil had signs of exhaustion by the Nursing team, as the literature found that nearly 56% of these professionals fell ill in the last 12 months, had accidents at work, and approximately 180,000 professionals in the last year feel unassisted.…”
Section: Signs and Symptoms Of Psychological Distress Studiesmentioning
confidence: 99%
“…2 Faced with this pandemic and critical situation, health professionals, and more specifically Nursing professionals, are at the forefront of care and attention to people with COVID-19, which can trigger psychological distress. 3,4 Chinese and national studies indicate that health professionals, mainly nurses, exposed to the COVID-19 disease during the epidemic period, suffered negative impacts on mental health [3][4][5][6] related to the labor context. 3,5 However, psychological distress affects and impacts the life of Nursing professionals in the psychosocial context and their general well-being, which denotes the relevance of identifying such situations of mental distress.…”
Section: Introductionmentioning
confidence: 99%
“…Os profissionais da linha de frente dos atendimentos pré-hospitalares (APH) estão mais expostos a riscos, inclusive biológicos, uma vez que atuam em ocorrências nas quais nem sempre possível ter ciência de casos suspeitos e/ou confirmados de doenças transmissíveis. Diante disso, torna-se imprescindível a implementação de amplas medidas preventivas antes, durante e após esses atendimentos, visando diminuir a exposição de pacientes e profissionais a doenças infectocontagiosas, como a COVID-19 (Marques et al, 2020).…”
Section: Introductionunclassified